Sectoral Price Effects of the Malaysian Economy - Abdul Rashid, Zakariah; Abdullah, Mohd. Zahid (Universiti Putra Malaysia Press, 1993)
The interdependence among industries makes prices of a commodity become costs to other commodities. The structural matrix of an economy may indicate such interdependence. This paper- analyses the effects on Malaysian sectoral prices of changes in the salary and wages, commodity taxes, non-wage incomes and intermediate imports. It further examines whether the price changes are significantly due to the volume of added value and industrial linkages. The results affirm the above question.